Peran Aspek Keuangan dalam Studi Kelayakan Bisnis Start-Up di Era Digital - Fadhil Musyafa; Ahlamul Jaris Gea; Irvan Maulana; Muhammad Hafiz; Mutiah Khaira Sihotang (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
A business feasibility study is an in-depth analysis process to assess whether a business or project is feasible to run. This process includes a review of various interrelated aspects, such as market aspects, finance, field facts, and other factors. The market aspect focuses on demand, supply, and competition in the market that is the target of the business, while the financial aspect assesses the business's ability to generate profits and meet financial obligations. Financial analysis involves planning funds, capital structure, and estimating costs and revenues needed for operations. Investment, financing, and dividend decisions are very important in managing a company's finances, especially for start-up companies. The use of analysis tools such as financial ratios and the Economic Value Added (EVA) method allows companies to assess their financial performance and efficiency. Risk analysis is also an important part of decision making to minimize potential losses. Overall, a business feasibility study helps companies plan long-term strategies, manage risks, and ensure the continuity and growth of their business.